A case report and literature review of multiple orthokeratinizing odontogenic cysts: The great mimicker. (5th April 2021) - Joseph, Jessica; Dungarwalla, Mohammed M.; Jones, Judith
Abstract: Background: Orthokeratinized odontogenic cysts are a rare type of odontogenic cyst, which are identified by an orthokeratinized stratified squamous epithelium. These cysts were originally classified as a subtype of odontogenic keratocysts; however, they have been redefined as a distinct entity. They radiographically mimic dentigerous cysts which can confound the final diagnosis. Most of the literature describes cases of single OOC, with far fewer cases of multiple orthokeratinized odontogenic cysts being reported. Method: This paper details a case of multiple orthokeratinized odontogenic cysts in a patient and compares their presentation to other cases of multiple orthokeratinising odontogenic cysts reported in the literature. Results: Six previous cases of multiple orthokeratinized odontogenic cysts were identified in the literature. The majority of features were similar to the case presented, with most cysts occurring in the mandible, in males in their third decade. In all but one of the cases, these cysts were also associated with unerupted teeth. Discussion: Orthokeratinizied odontogenic cysts display similar features to other odontogenic cysts. However, they possess distinctly different features to odontogenic keratocysts in their histopathology, presentation and recurrence rate. Conclusion: Orthokeratinized odontogenic cysts should be considered as a radiographical differential diagnosis for a dentigerous cyst and a histopathological differential diagnosis for odontogenic keratocyst.